Modern aspects of photodynamic therapy of actinic keratoses - I. V. Reshetov; A. S. Fatyanova; Yu. V. Babaeva; M. M. Gafarov; K. V. Ogdanskaya; T. E. Suhova; S. V. Korenev; M. V. Denisenko; Yu. S. Romanko (Biomedical Photonics, 2019)
Currently, photodynamic therapy (PDT) remains the most effective treatment for actinic keratosis (AK). With the increase in the incidence of AK, mainly due to the popularization of recreation in countries with increased insolation, there is an increasing interest in developing new methods of diagnostics and treatment and improving the existing ones. Studies that are aimed at determining the final efficacy of PDT, taking into account the resulting adverse reactions and long-term cosmetic results, are becoming increasingly popular. The nature of the light needed to excite a photosensitizer (PS) opens up new possibilities in the field of experimental studies that are aimed at reducing adverse reactions with similar efficacy of the applied therapy. In the review article, we presented the results of our own and foreign studies on the diagnosis and treatment of AK for 2017–2019, namely: we determined the possibilities of using sources with natural and short-wave radiation at different depths of skin lesions; presented a classification of the growth of AK in the basal layer of the epidermis, which increases the possibility of predicting the outcomes of the disease; showed the prevailing efficiency of fluorescent diagnostics compared with traditional diagnostic methods; evaluated the advantages of PDT using natural light and artificial sources of radiation; described the possibility of using a combination of drugs to increase the effectiveness of PDT in difficult to treat areas and in AK foci with a high degree of damage to the basal layer of the epidermis.